(untitled) (8gen-ART, 2023)
Çallı, a mountain village in Burhaniye District of Balıkesir Province, is 9 km from Burhaniye district center by road. It is located in the distance. Roughly 426 m from the sea level, on the steep western slopes of the Madra Mountains, overlooking the Burhaniye and Edremit Plains and the shining sun of the Edremit Gulf. The village rapidly lost its population after the 1990s, and today it looks like a completely deserted and abandoned village, except for four households. Unused and abandoned stone masonry walls and earthen roofed structures are also turning into ruins day by day due to neglect. Çallı Village, which is melting like soap, has a settlement texture perfectly adapted to the topography on a slope resembling the ancient theater cavea. The current situation of the settlement was documented with photographs and drawings, and some civil architecture examples that survived until today were examined in terms of plans and materials, and architectural documentation and archive studies were carried out. In this research, in addition to documentation studies, personal interviews were conducted with local people and the living habits of the region were documented. Suggestions have been made to document the rural architectural examples of Çallı Village and to preserve them and pass them on to future generations. It is thought that it will contribute to the literature.